PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP YIELD SUKUK DENGAN PERINGKAT SUKUK SEBAGAI VARIABEL INTERVENING (Study Pada Perusahaan Non Keuangan di Bursa Efek Indonesia ) - Leily Hamida (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2017)
This research aims to analyze the impact of liquidity ratio (current ratio), leverage ratio (debtto equity ratio) toward yield to maturity and sukuk rating. The sample that used was sukukthat listed in Indonesian Stock Exchange and it was rated by PT PEFINDO during 2006-2014.The technique that used to select the sample was purposive sampling. Based on this method,there are 29 companies that were suitable with the criteria. The analysis method that used inthis research was multiple analysis linier regression with intervening variable. The result of thisresearch was Sukuk Rating and Debt to Equity Ratio (DER) variables had significant negativeimpact to Yield To Maturity. But, liquidity (current ratio) did not give significant impact to Yield ToMaturity, liquidity (current ratio) variables brought significant negative impact to sukuk rating andleverage (debt to equity ratio) did not give impact to sukuk rating too.Keywords : Current Ratio, Debt To Equity Ratio, Sukuk Rating, Yield To Maturity